Flexible dielectric polymer nanocomposites with improved thermal energy management for energy-power applications - Uyor, U. O.; Popoola, A. P. I.; Popoola, O. M. (Frontiers in Energy Research, 2023)
Most polymer materials are thermal and electrical insulators, which have wide potential in advanced energy-power applications including energy conversion. However, polymers get softened when in contact with heat, which causes their molecular chains to flow as the temperature increases. Although polymer dielectrics exhibit high power density, they face challenges of low energy density which is due to the low dielectric permittivity associated with them. Therefore, this study tried to address the poor thermal energy management and low energy density of poly (vinylidene fluoride) (PVDF) while maintaining its flexible property using low content of hybrid carbon nanotubes (CNTs–0.05wt%, 0.1wt%) and boron nitride (BN–5wt%, 10wt%) nano-reinforcements. The nanocomposites were developed through solvent mixing and hot compression processes. The dielectric constant increased from 9.1 for the pure PVDF to 42.8 with a low loss of about 0.1 at 100 Hz for PVDF-0.1wt%CNTs-10wt%BN. The thermal stability of the nanocomposites was enhanced by 55°C compared to the pure PVDF. The nanocomposites also showed improved melting and crystallization temperatures. The developed PVDF-CNTs-BN nanocomposites showed significant enhancements in thermal energy management, stability, and dielectric properties. The significantly improved properties are credited to the synergetic effects between CNTs and BN in the PVDF matrix in promoting homogeneous dispersion, thermal barrier, interfacial polarization/bonding, insulative and conductive properties. Therefore, the developed nanomaterials in this study can find advanced applications in the energy-power sector owing to their enhanced performances.